Investigation of a Relation between Radiogenic Heat Production Rate (RHPR) and Land Surface Heat Temperature (LST) from Thermal Bands of ASTER and Landsat-8 (TIR-Data): Case Study of West Ras Gharib area North Eastern Desert, Egypt - Samah Saeed Abdeen; Sami Hamed Abd El Nabi; Moataz El said El Manawy; Reda Esmat El-Arafy; Karam Samir Farag (Indonesian Journal of Geography, 2022)
In this paper, an attempt was tried to study the relation between the land surface heat temperature (LST), extracted, from the thermal emission infrared data (ASTER-TIR) and (Landsat-8-TIR) imagery and radiogenic heat production rate (RHPR) that calculated from airborne gamma-ray spectrometric data applied on west Ras Gharib area at Northeastern Desert of Egypt. The area is geologically covered mainly by Precambrian basement rocks, which are unconformably overlain by Phanerozoic sedimentary succession. The method used for extraction land surface heat temperature for both ASTER-TIR and Landsat-8-TIR images is the reference channel emissivity technique and founded as the best method comparing to others. The study results showed a relative higher RHPR threshold value reached 4.8 μW/m3. On the other hand, ASTER-TIR Land Surface Temperature (AST-LST) ranges between 27.64oC to 47.2oC and, the Landsat 8-TIR Land Surface Temperature (LS8-LST) ranges between 30.64oC to 50.68oC. Comparing all results, there were a weak relationship or to some extent parallel relation between RHPR and satellite LST; as when the value of the Y-axis is constant, there are multiple values on X-axis, so it is not possible to deduce the value of one variable in terms of the other. The poor relation is regarded to the very weak RHPR which is not enough to affect the surface heat temperature, emission that could be detected by both thermal sensors of ASTER and Landsat-8 satellite TIR data. Other factors such as: topography, wind, shading and scattering, rock moisture and density, can strongly affect the surface temperature. In conclusion, the output results could be improved in areas of very high radioelement concentrations especially 235U, and through the use of the enhanced spatial resolution of future satellite TIR imaging instruments.